Temporary Workers Are Not Free-Riders: An Experimental Investigation - Davide Dragone; Fabio Galeotti; Raimondello Orsini (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2013)
We conduct an artefactual field experiment to study whether the individual preferences and propensity to cooperate of temporary workers differ from permanent contract workers. We find that temporary and permanent contract workers have different other-regarding preferences, but display similar contribution patterns in an anonymous Public Good Game. Students, instead, are more selfish and contribute less than temporary and permanent workers.
Keywords: C72; C93; D23; H41; J54; 330